STRATEGI MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PENDEKATAN OUTDOOR LEARNING DI MADRASAH IBTIDAIYAH - Riadi Riadi; Katni Katni (Universitas Muhammadiyah Ponorogo, 2022)
The purpose of this study is to analyze the increase in student learning motivation through the outdoor learning approach, analyze strategies for increasing student learning motivation through the outdoor learning approach and determine the factors that influence the increase in learning motivation through the outdoor learning approach in Madrasah Ibtidaiyah. This study uses a qualitative approach with a field research type to obtain in-depth data on strategies for increasing student learning motivation through the outdoor learning approach in Madrasah Ibtidaiyah. Data collection techniques include observation, interviews, and documentation, which are then analyzed thematically to identify related patterns and themes. This study was conducted at Madrasah Ibtidaiyah Islamic Center Ponorogo which has implemented outdoor learning, involving teachers, students, and the principal as informants. The findings of this study indicate that the outdoor learning approach at this Madrasah increases student motivation through nature-based learning, instilling religious and ethical values, and implementing internal and external strategies. Supporting factors include strategic location, tutoring activities, and institutional awareness. However, limited land and a lack of community understanding are inhibiting factors. Promotion and outreach of nature-based education are needed to increase student motivation.